1995
DOI: 10.1016/0378-1097(94)00514-r
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position of Rickettsia tsutsugamushi and the relationship among its antigenic variants by analyses of 16S rRNA gene sequences

Abstract: The 16S rRNA gene sequences of Rickettsia tsutsugamushi and Rickettsia sibirica were determined by PCR and DNA sequencing. Phylogenetic analysis revealed that R. sibirica is positioned in a cluster of the genus Rickettsia with a similarity value of 98.1-99.6%, whereas R. tsutsugamushi is located apart from the cluster with a similarity value of 90.2-90.6%. This evidence suggests that R. tsutsugamushi should be excluded taxonomically from the genus Rickettsia. The phylogenetic classification of six antigenic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 7 publications
3
24
0
2
Order By: Relevance
“…Because the 16s rRNA genes of the Gilliam, Karp, Kato, and Kuroki strains are ≥ 98.4% homologous, 29 this gene is useful for differentiating between Orientia and other genera/species, but not between O. tsutsugamushi strains. It has been reported that the 56-kDa protein gene is more useful for differentiating between O. tsutsugamushi strains than the 16s rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Because the 16s rRNA genes of the Gilliam, Karp, Kato, and Kuroki strains are ≥ 98.4% homologous, 29 this gene is useful for differentiating between Orientia and other genera/species, but not between O. tsutsugamushi strains. It has been reported that the 56-kDa protein gene is more useful for differentiating between O. tsutsugamushi strains than the 16s rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have also shown that O. tsutsugamushi is closely related to but separate from Rickettsia spp. 2 The phylogenetic trees generated using the 16s rRNA gene did not show good resolution of O. tsutsugamushi phylogeny for characterizing evolutionary relationships between different O. tsutsugamushi strains or types caused by the low mutation rate of the 16s rRNA gene, therefore, the DNA variation within the gene could not resolve and characterize O. tsutsugamushi isolates variation. 41 However, the hyper variable region of the 56-kDa TSA gene of O. tsutsugamushi evolves faster and carries a higher mutation rate and therefore was chosen and used for resolving and characterizing evolutionary relationships of each isolate.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3] Orientia tsutsugamushi is a member of the family Rickettsiaseae in the Proteobacteria α-subdivision based on 16s ribosomal RNA (rRNA) gene homology classification. 2,4 The bacterium size is ~0.5 μm wide and 1.2-3.0 μm long.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations